The Development of Extradosed Bridge Concept from a Vision to a Reality - Teddy S. Theryo (Institute of Research and Community Outreach - Petra Christian University, 2021)
The development of Extradosed bridge from a vision to a real project is presented in this paper. Mathivat of France who is recognized as the inventor of this bridge type, envisioned a new bridge type suitable for medium span ranges in 1979. He suggested that some of the cantilever tendons in balanced cantilever bridge can be deviated to the top deck supported by short tower resemble stay cables. The structural benefit of this idea is increasing positive moment capacity by increasing eccentricity over the pier and enhanced shear capacity. Therefore, with the same conditions, longer span can be designed. Due to small angle of stay cables, the cable allowable stress at serviceability is about the same level with balanced cantilever bridge and no significant penalty on fatigue resistance unlike stay cables for conventional cable stayed bridges. The Extradosed bridge offers economic benefit for medium span range and aesthetically pleasing.